Isolation of Flavonoid Compounds from Bangun-bangun Leaves (Plectranthus amboinicus (Lour.) Spreng.) - Lenny, Sovia (Journal of Chemical Natural Resources, 2021)
Isolation of flavonoid compounds from leaves of Bangun-bangun (Plectranthus amboinicus (Lour.) Spreng.) has been conducted by maceration process with methanol solvent, added with ethyl acetate, and then partially extracted with n-hexane, acided by HCl 6% and partition extracted with chloroform. The concentrated extract of chloroform was separated using column chromatography with eluent n-hexane: ethyl acetate. The resulted tawny paste yielding was 10 mg with Rf= 0.38. The resulted compounds were characterized using UV-Vis, FT-IR, and 1H-NMR which was estimated as a flavonoid is a flavanone.